2012
DOI: 10.1242/dev.071555
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of synapse formation by Wnt-induced MuSK endocytosis

Abstract: In zebrafish, the MuSK receptor initiates neuromuscular synapse formation by restricting presynaptic growth cones and postsynaptic acetylcholine receptors (AChRs) to the center of skeletal muscle cells. Increasing evidence suggests a role for Wnts in this process, yet how muscle cells respond to Wnt signals is unclear. Here, we show that in vivo, wnt11r and wnt4a initiate MuSK translocation from muscle membranes to recycling endosomes and that this transition is crucial for AChR accumulation at future synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 87 publications
(113 reference statements)
7
56
0
Order By: Relevance
“…During this step, early nerve-induced signaling is occurring, many AChR clusters are not yet innervated and both aneural and neural AChR clusters can be visualized and quantified, and thus the AChR defects observed are likely to result from initial nerve-independent postsynaptic differentiation. In line with this, Granato and colleagues showed that both Wnt11r and Wnt4a are required for AChR prepatterning in zebrafish and we previously reported that Wnt4 participates in aneural AChR clustering in mice (Gordon et al, 2012;Strochlic et al, 2012). However, only the combined inactivation of wnt11r and wnt4a in zebrafish led to a complete loss of aneural AChR clusters, and loss of Wnt4 function in mice did not fully abolish muscle prepatterning.…”
Section: Coordinated Roles Of Wnt4 and Wnt11 In Achr Clusteringsupporting
confidence: 71%
See 4 more Smart Citations
“…During this step, early nerve-induced signaling is occurring, many AChR clusters are not yet innervated and both aneural and neural AChR clusters can be visualized and quantified, and thus the AChR defects observed are likely to result from initial nerve-independent postsynaptic differentiation. In line with this, Granato and colleagues showed that both Wnt11r and Wnt4a are required for AChR prepatterning in zebrafish and we previously reported that Wnt4 participates in aneural AChR clustering in mice (Gordon et al, 2012;Strochlic et al, 2012). However, only the combined inactivation of wnt11r and wnt4a in zebrafish led to a complete loss of aneural AChR clusters, and loss of Wnt4 function in mice did not fully abolish muscle prepatterning.…”
Section: Coordinated Roles Of Wnt4 and Wnt11 In Achr Clusteringsupporting
confidence: 71%
“…In zebrafish, both Wnt4a and Wnt11r initiate muscle prepatterning, probably by stimulating PCP-dependent MuSK endocytosis in muscle cells (Gordon et al, 2012;Jing et al, 2009). In mice, although recent data have challenged the role of Wnts at the NMJ (Remédio et al, 2016; discussed below), we have demonstrated that Wnt4 contributes to muscle prepatterning (Strochlic et al, 2012).…”
Section: Introductionsupporting
confidence: 45%
See 3 more Smart Citations